Obvious manipulations in cake-cutting - Josué Ortega; Erel Segal-Halevi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
In cake-cutting, strategy-proofness is a very costly requirement in terms of fairness: for n = 2 it implies a dictatorial allocation, whereas for n Ï 3 it requires that one agent receives no cake. We show that a weaker version of this property recently suggested by Troyan and Morril, called not-obvious manipulability, is compatible with the strong fairness property of proportionality, which guarantees that each agent receives 1/n of the cake. Both properties are satisfied by the leftmost leaves mechanism, an adaptation of the Dubins - Spanier moving knife procedure. Most other classical proportional mechanisms in literature are obviously manipulable, including the original moving knife mechanism. Not-obvious manipulability explains why leftmost leaves is manipulated less often in practice than other proportional mechanisms.
Keywords: D63; D82; 330; cake-cutting; not-obvious manipulability; prior-free mechanism design